Silent Witness 2020
DOI: 10.1093/oso/9780190909444.003.0016
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Genetics, Ethics, Privacy, and Public Policy

Abstract: Chapter 15 covers various ethical issues associated with the use of DNA methods for forensic analyses and human rights investigations. Topics include informed consent and storage issues for samples and profiles; data security and privacy; identification of individuals using aggregate data from forensic, genealogical, research, or clinical databases; the burden of the obligation to report incidental findings that are medically actionable; cultural perspectives on genetic information; government misuse of potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In this regard, it is necessary that governments seek advice on how to influence public policy based on evolving genetic knowledge, and scientists should be involved in this process, as communicated in van Heyningen and Cox (2002) [24]. Authors have also reported, as noted by Lee (2020) and Teodorović et al (2017) [18,20], that, since the more science that evolves, the more information that is extrapolated by the genes, consequently genetic privacy, along with the ethical issues regarding it, needs to be re-examined.…”
Section: Ethical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is necessary that governments seek advice on how to influence public policy based on evolving genetic knowledge, and scientists should be involved in this process, as communicated in van Heyningen and Cox (2002) [24]. Authors have also reported, as noted by Lee (2020) and Teodorović et al (2017) [18,20], that, since the more science that evolves, the more information that is extrapolated by the genes, consequently genetic privacy, along with the ethical issues regarding it, needs to be re-examined.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…Ethical, social, and legal concerns are always raised when sensitive and identifying personal data are collected, stored, and used [19]. Along with the evaluation of informed consent, genetic privacy is an important ethical issue that needs to be addressed and revisited on a regular basis, as research and technology continue to expand our technical capabilities [20]. In fact, forensic scientists, bioethicists, law enforcement agencies, genetic genealogists, and other interested parties should collaborate in the development of international policies and guidelines for best practices [21,22].…”
Section: Introductionmentioning
confidence: 99%